Partial molecular characterization of Sm8, a tegumental antigen of Schistosoma mansoni - Frederico GC Abath; Edeneide M Xavier; Sílvia ML Montenegro; Roberto P Werkhauser (Memorias do Instituto Oswaldo Cruz, 2002)
Sm8 is a major tegumental antigen of Schistosoma mansoni. The partial cDNA was isolated and analyzed. Sequence analysis revealed transmembrane compatible hydrophobic domains and a putative leucine zipper pattern. The mRNA and the protein are predominantly expressed in adult worms.